Digital Transformation Development Trends in Armenia - Sargsyan, Varsеnik; Gevorgyan, Ruben; Avetisyan, Karine; Minasyan, Karine (Bulletin of Yerevan University G: Economics, 2022)
The development of high technologies has a decisive role in increasing the competitiveness, security and living standards of the state. The aim of the research is to reveal the development trends of digital technologies in Armenia, in particular, how widespread digital tools are, how much they have changed over time, what technical problems arise when using digital tools, which platforms are more effective for the economy: online or offline. In recent years, all the countries of the world have introduced the principle of e-governance to one degree or another in the field of public administration, the purpose of which is to increase the efficiency of processes through the use of digital technologies, particularly by minimizing the physical contacts of civil servants and citizens. It is obvious that these processes are not only technological in nature and are conditioned by the degree of development of digital technologies in this or that country, but also by the possibilities of new regulations for improving economic relations and even changing business habits and people’s behavior. Digital technologies have greatly influenced the world economy, expanding the information base, reducing the costs of information collection, contributing to the formation and progress of electronic commerce, reflecting on the life, activities, thinking, customs, communication of the society, promoting the innovative development of the economy.
Keywords: digitalization; digital technologies; electronic platform; financial markets; focus group; public administration; information processing; e-commerce; expert request